Iupac handbook 1998-99 - IUPAC ([S.l.] : Wiley-Blackwell, 1998)
The 1998-1999 IUPAC Handbook contains not only the membership of Standing Committees, Divisions, Commissions etc., but also the projects on which the IUPAC bodies are working. The Statutes and Bylaws of the Union and the Rules and Terms of Reference of the Divisions/Committees are reproduced in toto. The Handbook is intended to provide detailed information on the membership, working programmes of the Union, and the rules of operation in one volume, and will be a useful reference source for chemists and chemical organisations worldwide.
Keywords: handbook